Variational hysteresis and photoresponse behavior of MAPbX3 (X = I, Br, Cl) perovskite single crystals. (3rd June 2021) - Lin, Ping; Meng, Qingyu; Chen, Hang; Hu, Haihua; Fang, Desheng; Xu, Lingbo; Wang, Peng; Cui, Can
Abstract: High-quality MAPb X 3 ( X = I, Br, Cl) single crystals with a desirable size were grown through an inverse temperature crystallization method. Systematically measurements of current–voltage ( I – V ) hysteresis show that the hysteresis is strongly dependent on the measuring protocol, including scan rate and light illumination condition, which reveals the competition of three main factors that influence the charge dynamics in different regimes, defect trap, MA + dipoles rotation, and ion migration. In the dark, defect trapping is the dominant charge transport dynamics at low bias in the MAPbI3, while the MA + dipole rotation is significant in MAPbBr3, and ion migration occurs in MAPbCl3 . However, as bias increases, MA + dipole rotation plays a crucial role in the conductivity either in the dark or under light illumination. The time-dependent photoresponse exhibits different tendencies under various biases. The slow rising dynamics of photoresponse in MAPb X 3 is attributed to the slow rotation of MA + dipoles, while an immediate overshoot followed by a decay suggests significant ion migration contribution at high external bias. The results serve as comprehensive experimental support to understand the hysteresis behaviors and slow photoresponse in MAPb X 3, particularly in MAPbCl3, and provide a guide for future work in MAPb X 3 based optoelectronic devices.